SOCIAL MEDIA, CYBER-DISSENT, AND CONSTRAINTS ON ONLINE POLITICAL COMMUNICATION IN CENTRAL ASIA - J. Bowe, Vrian; Freedman, Eric; Blom, Robin (CENTRAL ASIA AND THE CAUCASUS, 2012)
Recent world events have demonstrated that the Internet—and social media tools in particular—are increasingly useful for political organizing, not merely frivolous virtual spaces for youthful publics to connect socially. Rather, social media is touted as “the crucible in which repressed civil societies can revive and develop.” For the people of Central Asia—where free expression is curtailed and news outlets are under official or non-state, non-official government censorship—information and communication technology (ICT) provides an increasingly important vehicle for political expression. Blogging and social media tools may fulfill a crucial role for non-journalists and oppositional groups that journalism serves in more democratic societies, as recent events in Tunisia, Egypt, and Iran illustrate. In earlier eras, the costs associated with traditional or legacy media necessarily limited participation to small groups of elites. Now, the relative lack of entry costs in the online world raises the prospects for mass publics to bypass those traditional gatekeepers and become publishers and broadcasters on their own. ICTs have “had clear roles in both starting new democratic processes in some countries and entrenching them in others,” Howard noted. However, the libertarian possibilities of increased freedom facilitated by ICT access have a dark reality, as repressitarian governments adapt to the Internet age by exerting power over the Internet’s infrastructure and using activist communications for surveillance purposes. This paper reviews recent events and legal developments related to the Internet and social media in Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. They include legislation extending libel laws to online communications, blocking of oppositional and independent websites, and punishing journalists who report or comment for online media.